THE ROLE OF ANALYTICAL CHEMISTRY IN THE FORMATION OF PROFESSIONAL COMPETENCES IN THE TRAINING OF PHARMACIST STUDENTS - Крупко, Олена (Modern engineering and innovative technologies, 2023)
The paper describes the role of the discipline "Analytical Chemistry" in the preparation of masters of pharmaceutical education, assimilation and acquisition by them specified in the educational and professional program "Pharmacy" of the second (master's